PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN KEPEMILIKAN ASING TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Adhiwardana, Edoardus Satya; Daljono, Daljono (Diponegoro Journal of Accounting, 2013)
The purpose of this research is to test the effect of CSR and foreign ownership on financial performance. Data collecting is using of purposive sampling method for manufactur companies listed in Indonesia Stock Exchange in. A total of 66 manufactur companies are used as a sample. The method of analysis of this study use multiple regression. The results of this research indicate that the CSR and foreign ownership have a significant effect on firm performance.